Immunogenetics of Celiac Disease: A Focus on Arab Countries - Younes, Nadin; Younes, Salma; Alsharabasi, Ola. A.; El Zowalaty, Mohamed E.; Mustafa, Ibrahim; Jahromi, Mohamed; Uddin, Shahab; Al-Nesf, Mariam; Pintus, Gianfranco; Zayed, Hatem (Current Molecular Medicine, 2020)
Celiac Disease (CD) is a complex immunogenic disease mainly triggered by gluten intake in genetically susceptible individuals with a prevalence of 1 in 100-300. CD results from the interplay between genetic and environmental factors. Genetic susceptibility is believed to play a prominent role in the pathogenicity of CD, mainly due to human leukocyte antigen (HLA)-related class II genes. Although CD is wellrecognized among Arab populations, there are few studies on the genetic epidemiology and prevalence of CD in the Arab countries. Therefore, the aim of this review was to highlight the importance of studying this disease in the Arab world in the context of a global perspective. Within the few studies published so far, it was found that Arab populations have a distinctive susceptibility genetic profile from other ethnic groups with the DQ2.5 and DQ8 genotypes that are considered the major genotypes that confer susceptibility among Arab patients with CD. Our findings will pave the way to perform further epidemiological studies that will help identify potential therapeutic targets against CD among Arab patients that are diagnosed with CD.
Keywords: HLA